Information Technology Capability and Its Impact on Firms Performance - Lejla Turulja; Nijaz Bajgorić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
According to the resource-based view, sources of competitive advantage begin with the notion that differences in performance are fundamentally due to the distinctive resources and capabilities that are valuable, rare, inimitable and nonsubstitutable (Barney, 2007; Wu et al., 2006). Information technology (IT) as a resource of the company has the increasing importance for the researches and managers. Research on the IT value within organizations and firms' IT capabilities have expanded over the past decade (Pérez-López et. al., 2012). Tippins and Sohi (2003) in their study defined IT capability as the existence of IT infrastructure, IT knowledge and IT operations within company. The purpose of this paper is to analyze the impact of IT capability on firms' innovativeness and the relationship among IT capability, firms' innovativeness and business performance. The study uses survey data from managers and structural equation modelling to assess the relationships between IT capability, firms' innovativeness and business performance. This study finds that both IT capability and innovation capability play important role in achieving greater business performance. The findings indicate that managers should focus on development of the IT function within company, taking into account importance of IT investment as well as IT knowledge, and promotion of innovativeness.
Keywords: M15; 330; Information Technology Capability; Innovation; Innovativeness; Resource Based Theory; Performance; Dynamic Resource View